Parametric review of existing regolith excavation techniques for lunar In Situ Resource Utilisation (ISRU) and recommendations for future excavation experiments. (January 2020) - Just, G.H.; Smith, K.; Joy, K.H.; Roy, M.J.
Abstract: A high-level overview of current research in the area of lunar regolith excavation and handling for In Situ Resource Utilisation (ISRU) is presented. Thirteen processes are grouped into discrete and continuous excavators. A further differentiation is made between systems with and without connection to a mobility platform – referred to as complete and partial systems. For each group, a set of representative performance parameters has been identified and compared, while special characteristics or limitations are highlighted. The present work identifies a need for high detail research into the development of reliable and efficient excavation systems, due to the high importance of regolith excavation and handling to ISRU. A need for more standardised information and recording of specific data during supporting experimental studies is made apparent. In order to enable easier categorisation, comparison, and evaluation of future concepts, a set of key performance parameters requiring consideration during experimental campaigns is described and the importance of their inclusion underlined. Highlights: An overview of current research into lunar regolith excavation for ISRU is presented. Thirteen excavation techniques reviewed using four system classes and six parameters. A need for more standardised recording of performance data during experiments is apparent. A set of key metrics is suggested, enabling easier concept categorisation and comparison.